Neuromuscular electrical stimulation (NMES) and oral sensorimotor stimulation in a young child with cerebral palsy and severe dysphagia - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2015)
Dissertation (MComm Path)--University of Pretoria, 2015.